Makalah Manajemen Proyek Informatika - Angelica Crystastelia; Rendy Satria Pradja; Siti Aripah; Raviyanto Aji Permana (CV. Multi Kreasi Media, 2024)
Management in general is an attempt to achieve a goal with minimal resources (efficient). Meanwhile, a project is a work plan with a certain achievement target that is completed within a certain time frame. Collectively, project management is an approach/method for managing a project effectively and efficiently. This system exists as a tool to help manage projectshaped activities, such as construction projects. Without it, a project will be difficult to execute in terms of cost, time, or even quality.